Are functional movement disorder phenotypes or age at onset correlated with perfectionism or history of abuse?. (2021) - Mehanna, Raja; Zhu, Liang; Bejjani, Carla
Highlights: Charts of 56 patients with Functional Movement Disorders (FMD) were reviewed. 30(53.6%) had perfectionism (P), 27(48.2%) had history of childhood abuse (CA). 4(7.1%) denied P, CA or any psychiatric comorbidity. No correlation was detected between each of the FMD phenotypes and P or CA. No correlation was detected between the age at symptoms onset and P or CA. Abstract: Objective: To assess if the phenotype or age at onset of Functional Movement Disorders (FMD) vary as a function of presence of a perfectionism or history of abuse. Detecting such a potential association might help guide future research into the pathophysiology of FMD. Methods: Charts of all patients diagnosed with FMD by a movement disorder specialist using the commonly accepted clinical diagnostic criteria for FMD seen at a tertiary center over 8 years were reviewed. Data collected were sex, age at the onset of the first FMD, phenotype of the first predominant FMD, history of perfectionism and history of childhood abuse (physical, sexual, emotional, or neglect). Statistical analyses were performed as appropriate. Results: 68 patients with FMD were identified from which 12 were excluded for incomplete documentation. 56 patients were included in the analysis, 43 (76.8%) were women, with average age at onset 41.5y (range 13–74.4). The most frequent predominant initial FMD phenotypes were tremor (39%), dystonia (20.3%) and gait disorders (20.3%).Perfectionism was reported in 30 (53.6%) patients and history of abuse in 27 (48.2%).There was no significant correlation between each of the FMD phenotypes and perfectionism or history of childhood abuse. There was also no correlation between the age at symptoms onset and perfectionism or history of abuse. Conclusion: We could not demonstrate a significant correlation between FMD phenotype or age at onset and perfectionist personality trait or history of abuse. Factors leading to the development of one specific FMD phenotype rather than another are still to be elucidated.